Comparing the Chemical Structure and Protein Content of ChEMBL, DrugBank, Human Metabolome Database and the Therapeutic Target Database. Issue 11 (11th December 2013) - Southan, Christopher; Sitzmann, Markus; Muresan, Sorel
Abstract ChEMBL, DrugBank, Human Metabolome Database and the Therapeutic Target Database are resources of curated chemistry‐to‐protein relationships widely used in the chemogenomic arena. In this work we have extended an earlier analysis (PMID 22821596) by comparing chemistry and protein target content between 2010 and 2013. For the former, details are presented for overlaps and differences, statistics of stereochemistry as well as stereo representation and MW profiles between the four databases. For 2013 our results indicate quality improvements, major expansion, increased achiral structures and changes in MW distributions. An orthogonal comparison of chemical content with different sources inside PubChem highlights further interpretable differences. Expansion of protein content by UniProt IDs is also recorded for 2013 and Gene Ontology comparisons for human‐only sets indicate differences. These emphasise the expanding complementarity of chemistry‐to‐protein relationships between sources, although different criteria are used for their capture.